The use of play-based activities among preschool teachers in the ministry of education (MOE) preschools in their teaching - Teo, Fang Liang (UNIMAS, 2009)
This study aimed to look at the use of play-based activities among 20 preschool teachers in 12 different Ministry of Education (MoE) preschools in Kuching divisions. The investigation was analyzed into three areas; the type of play-based activities used by the preschool teachers in their teaching where the chosen play-based activities were categorized based on Smilansky’s(1968)four types of play activities; the reasons for using the selected play-based activities and the type of retention activities given to the preschoolers. This study used the ideas proposed by Maria Montessori (1906) where she believed that children should be taught through the use of activities that can stimulate their learning interest. Meanwhile Jean Piaget (1962) believed that through play-based activities, children who aged between four to six were able to assimilate and accommodate the taught knowledge and skills. The combination of direct observation and semi- structured interview questions were used to gather the data. The direct observation looked at the activities used by the preschool teachers, the subject matter taught, the ways preschool teachers gathered preschoolers’ attention, the responses given by preschoolers and the selected retention activities used by the preschool teachers. While the semi-structured interview questions were used to get preschool teachers’ reasons for using the selected play-based activities. From the findings gathered, 15 out of 20 activities carried out by the preschool teachers were defined as play-based activities such as coloring activities, manipulation of colored papers and physical activities. Three ways usually used by preschool teachers to gather preschoolers’ attention were: by directly calling the preschoolers’ names, through the use of questions and non-verbal responses such as touching the preschoolers’ shoulders, hand clapping and hand waving. Five reasons why preschool teachers used the selected play-based activities had been identified:related to the subject matter taught, suitable for the preschoolers’ ages and abilities, memorization, developing preschoolers’ language development,and enhancing preschoolers’ muscle and eye coordination. Three type of retention activities commonly given to preschoolers to enhance what preschoolers had learnt: tasksheets, workbooks,and other types of play-based activity. In conclusion, the use of a play-based activity is one of the alternatives that provide fun learning for preschoolers to learn what had been taught to them.